2011
DOI: 10.1007/s00405-011-1727-3
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic DCR without stents: clinical guidelines and procedure

Abstract: It is a retrospective analysis of cases of endoscopic Dacryocystorhinostomy (DCR) in whom stents were not inserted after completion of surgery for the last 2 years. Thirty-five patients were included in this study, and selection of patients was done depending on both clinical findings preoperatively and on the operative findings during surgery. These criteria ensure that the level of obstruction is postsaccal, and good surgical procedure with maximal sac exposure and marsupialization. When all criteria were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Most common complication noted was hemorrhage, which conforms to the other reported studies, and has been managed well by us. 3,8 Cosmetically visible scar formation following Ex-DCR was reasonably low in our study (3/55 Ex-DCR; 5.45%, χ2=1.263) as compared to the published reports where visible scar formation ranges from 9-26%, hence this should not become a major issue and lone decisive factor while choosing for particular type of surgery ( Figure 5,6). 19,20 It is now an established fact that, surgical expertise in the field of DCR surgery may dramatically affect the surgical outcome.…”
Section: 12supporting
confidence: 57%
See 1 more Smart Citation
“…Most common complication noted was hemorrhage, which conforms to the other reported studies, and has been managed well by us. 3,8 Cosmetically visible scar formation following Ex-DCR was reasonably low in our study (3/55 Ex-DCR; 5.45%, χ2=1.263) as compared to the published reports where visible scar formation ranges from 9-26%, hence this should not become a major issue and lone decisive factor while choosing for particular type of surgery ( Figure 5,6). 19,20 It is now an established fact that, surgical expertise in the field of DCR surgery may dramatically affect the surgical outcome.…”
Section: 12supporting
confidence: 57%
“…Whereas, success rates for En-DCR reported vary from 74 to 100%, but may be complicated by nasal bleeding, nasal osteotomy scarring, granuloma, osteotomyturbinate/septal synechiae, CSF-rhinorrhea, and damage to the orbital contents. [2][3][4][5][6][7] Purpose of our study is to compare and analyze the surgical outcome of both Ex-DCR and En-DCR, in terms of their success, failure, and complications in a retrospective way, in our tertiary referral center of northern India. Patients and Methods: After obtaining approval from the Hospital medical ethics committee, retrospective data were collected, on patients who underwent DCR, for a period of two years from October 2013 to September 2015, at our medical college of north India.…”
mentioning
confidence: 99%
“…However, the use of silicone stenting during endoscopic DCR is a controversial topic. Some studies have reported that the silicone stent itself may cause tissue granulation, predisposing the site to postoperative infection, adhesions, and punctal lacerations and causing surgical failure [ 3 , 18 - 21 ]. Studies comparing endoscopic DCR with and without silicone intubation have been reported, and two meta-analyses concerning the benefits of silicone intubation during endoscopic DCR are available; however, the results are inconclusive [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years number of authors have described Endoscopic DCR without silicon stenting [12]. Though Smirnov [13,14] in his initial study mentioned a higher success rate with stenting, he subsequently corrected his own observations after 2 years and demonstrated that silicone stenting is unnecessary as his success rate with or without silicone tube was 78 and 100 % respectively.…”
Section: Discussionmentioning
confidence: 99%